Sport Hall Acoustics. (November 2015) - Iannace, Gino
A reciprocating compressor is commonly used in industry. However, because it is extremely noisy and harmful to the ears, a noise control mechanism is necessary. Eight kinds of noise control strategies used with the reciprocating compressor are explored, and COMSOL, a numerical analysis software, is adopted for acoustical analysis in the paper. The primary purpose of this research is to assess the influence of seven noise control strategies for the suction/discharge muffler of a reciprocating compressor. Results have shown that the noise control strategies can efficiently improve the acoustical performance of the suction/discharge mufflers. Sports halls are often used for musical shows, but they are primarily built for sporting events and the reverberation time values are often very high. In this paper acoustic measurements are reported inside a sport hall, the reverberation time measured is over 5.0 s at the middle frequencies, so it is unsuitable for musical shows. The acoustic correction is analysed with a software for the architectural acoustics; absorbent material under trusses and on the walls were considered, in this configuration the reverberation time calculated is about 2.6 s; the presence of audience is also analysed.